Analisis Arus Gangguan Hubung Singkat Pada Feeder Tampinna Gardu Induk Tegangan Ekstra Tinggi Wotu - Tasrif Tasrif; Andareas Pangkung; Dani Tri Ambarwati (Politeknik Negeri Ujung Pandang, 2023)
An electric power system is a complex system consisting of a powerplant, transmission system and distribution system that operates simultaneously in distributing electric power. In the distribution of electric power can not be separated from the occurrence of abnormal conditions of the system or disruption so that it needs a protection system to overcome the occurrence of interference. Disruption that often occurs in the electrical power system is a short circuit disruption so that a short circuit analysis is carried out as a first step in determining the right protection system. Short circuit disorder is a type of disruption that occurs in an electric power system due to an increase in excess current due to a decrease in the strength of isolation from the channel both between phases and between phases and earth. Tampinna feeder is one of the feeders in Wotu Extra High Voltage Substation. In this study will be calculated how much the current of short circuit interference in the feeder and the working time of the protection relay, namely OCR and GFR. From the calculation obtained a maximum short circuit disruption in three phases amounting to 771.86 A, two phases amounting to 668.45 A and one phase to the ground amounting to 370, 6 A.